Ethnobotany and intra-cultural diversity in the uses of Tephrosia vogelii (Fabaceae) in Centre Benin (West Africa) - Didolanvi, Luc; Chougourou, Daniel Chèpo; Azonkpin, Saturnin; Favi, Gnimansou Abraham; Akpo, Armand Akoutan (Ethnobotany Research and Applications, 2025)
Background: Rural dwellers harbor tremendous ancestral uses of local plant species, of which Tephrosia vogelii. This study aims to assess the use of diversity and the local perception of the temporal change of T. vogelii across the Fon ethnic group in central Benin. Methods: Ethnobotanical surveys were undertaken across three communes and six villages chosen based on species distribution and geographical distance between the villages. A total of 213 informants, including traditional healers, farmers, hunters, and herbalists, were randomly questioned using semi-structured interviews. The ethnobotanical indices, such as citation frequencies of use reports, use categories, preparation modes, and index value of organs, were calculated. The chi-square test was performed to assess whether the citations differed significantly between the communes prospected. Results: A total of 17 use reports were reported, ranging into six use categories, of which the medicinal (63.23%) uses represented the main category. Its use as firewood (20.26%) was the most cited use report and was followed by malaria treatment (17.65%) and abscess (11.11%). The index value of organs (IVO) highlights the leaves (41.65%) and leafy stem (16.2%) as the most important plant parts used. The decoction (50.2%) was reported as the main form of preparation of remedies. Conclusions: The Fon communities in central Benin locally use T. vogelii as a multipurpose plant species but report a decline in the species temporal abundance. As such, further research is needed for its sustainability and possible valorization. Keywords: Tephrosia vogelii, ethnobotanical uses, native plant, traditional knowledge, Benin.